(untitled) (Window of Public Health Journal, 2025)
Hypertension in adolescents refers to blood pressure that exceeds the normal range of 120/80 mmHg. To enhance early detection, it is essential to promote routine blood pressure checks at the nearest health service, preferably starting in the early morning. Several factors contribute to hypertension in adolescents, including sleep quality, diet (food intake), and smoking behavior. Hypertension in adolescents should receive serious attention. This study aims to determine the incidence of hypertension in adolescents and identify several factors related to this incidence among students at SMA Angkasa in Maros Regency. This type of research uses a quantitative design with a cross-sectional approach. Sampling in this study used simple random sampling with a sample size of 85 students. The instrument used was a questionnaire. The results of this study show that univariate analysis in grade X students of SMA Angkasa, Maros Regency, shows that sleep quality, diet, and smoking are associated with the incidence of hypertension. Bivariate analysis of sleep quality on hypertension shows that there is a relationship of ρ value 0.000 α ˂ (0.05), eating patterns on sleep quality in students with hypertension shows that there is a relationship of ρ value 0.012 α ˂ (0.05), and smoking behavior on sleep quality in students with hypertension shows that there is a relationship of ρ value 0.041 α ˂ (0.05).